2023
DOI: 10.1039/d3im00059a
|View full text |Cite
|
Sign up to set email alerts
|

Does the platinum-loading in proton-exchange membrane fuel cell cathodes influence the durability of the membrane-electrode assembly?

Ricardo Sgarbi,
William Ait Idir,
Quentin Labarde
et al.

Abstract: MEAs with various cathode Pt loadings were elaborated and aged using a multiple-stressor accelerated stress test (AST) in a segmented PEMFC. The thinnest (lowest Pt loading) cathodes have lower initial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…10−12 Recently, many efforts have shown that decreasing MEA electrode loadings is feasible for the anode side but not for the cathode side. 13 A primary cause of this problem is that the O 2 transport resistance of the low-Pt loading cathode is large, which leads to poor O 2 transfer efficiency and great voltage loss, particularly at high current densities, ultimately hindering the maximization of the catalyst performance in MEA. 14 One straightforward strategy for solving this problem is to reduce the thickness of the catalytic layer (CL) of the MEA, which can significantly shorten the average distance of the proton and oxygen transport path, thereby achieving efficient proton and oxygen transport.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10−12 Recently, many efforts have shown that decreasing MEA electrode loadings is feasible for the anode side but not for the cathode side. 13 A primary cause of this problem is that the O 2 transport resistance of the low-Pt loading cathode is large, which leads to poor O 2 transfer efficiency and great voltage loss, particularly at high current densities, ultimately hindering the maximization of the catalyst performance in MEA. 14 One straightforward strategy for solving this problem is to reduce the thickness of the catalytic layer (CL) of the MEA, which can significantly shorten the average distance of the proton and oxygen transport path, thereby achieving efficient proton and oxygen transport.…”
mentioning
confidence: 99%
“…Recently, many efforts have shown that decreasing MEA electrode loadings is feasible for the anode side but not for the cathode side . A primary cause of this problem is that the O 2 transport resistance of the low-Pt loading cathode is large, which leads to poor O 2 transfer efficiency and great voltage loss, particularly at high current densities, ultimately hindering the maximization of the catalyst performance in MEA. One straightforward strategy for solving this problem is to reduce the thickness of the catalytic layer (CL) of the MEA, which can significantly shorten the average distance of the proton and oxygen transport path, thereby achieving efficient proton and oxygen transport. , To maintain a constant cathode loading, reducing the thickness of the CL means requiring a catalyst with a higher Pt loading (weight percent), which is difficult to achieve, especially for structurally ordered Pt-based catalysts. , Typically, the synthesis of ordered alloy catalysts involves high-temperature annealing, which can trigger uncontrolled agglomeration of these alloys into large particles, thus decreasing the use of Pt and ORR catalytic activity. This problem becomes even more pronounced when dealing with a high Pt loading (>20 wt %) of catalysts, although coverage by inorganic coating layers (SiO 2 , , MgO, and TiO 2 ) and immobilization by salts (KCl and NaCl) have been employed to curb PtM nanoparticle (NP) aggregation during high-temperature pyrolysis processes.…”
mentioning
confidence: 99%